Analisis Kinerja Keuangan Pada PT. Indofood Sukses Makmur,Tbk - Thomas Khrisna Sidharta (LPPM Universitas PGRI Adi Buana Surabaya, 2022)
Financial statement analysis based on horizontal and vertical methods to find out the financial performance of PT. Indofood Sukses Makmur, Tbk. is running well or not. The data processed in this final project comes from the Indonesia Stock Exchange (IDX) in 2017 to 2019. The analytical method used is the vertical and horizontal analysis method. From the results of horizontal and vertical analysis on the income statement of PT. Indofood Sukses Makmur, Tbk. from 2017 to 2019 the percentage of net income and earnings per share in the comparison of 2017 with 2018 has decreased, but in the comparison of 2018 with 2019 the percentage of net income and earnings per share has increased